(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To analyze the influence of guidance work in pre-university settings on the development of comprehensive student well-being. Methodology: The research was performed in the Costa Rican Humanities School System (SCHC, its acronym in Spanish). It was carried out from a positivist and naturalistic paradigm, using a concurrent triangulation design with a non-probabilistic sample as a starting point. A total of 85 participants were selected based on the following criteria: representatives of SCHC executive directors and eleventh-year students. Results:Adolescence is influenced by a series of changes that affect the construction of identity and life plans. Therefore, the analysis of the information obtained confirms the functions that characterize the Guidance service in this educational modality and reflects the three dimensions of the comprehensive well-being circle that are prominent in guidance and collective interventions. Conclusions: To ensure the comprehensive well-being of students, the Guidance Department provides personalized services on various topics, such as the sense of identity and belonging, mental health, emotional regulation, decision-making, as well as an approach focused on adaptability in a transitional context, which facilitates understanding of the personal present and life design.